2017
DOI: 10.3906/tar-1609-41
|View full text |Cite
|
Sign up to set email alerts
|

Change of arginine content and some physiological traits under midseason drought in peanut genotypes with different levels of drought resistance

Abstract: Peanut production areas frequently suffer from drought, which can cause severe yield losses, increased aflatoxin, and compositional changes in seed. Midseason drought is generally the most detrimental to seed yields and in altering seed protein composition. The purpose of this study was to investigate the effect of midseason drought on arginine content in peanut genotypes with different levels of drought resistance. The experiment was conducted under field conditions for 2 years. Two water regimes (wellwatered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
4
1
Order By: Relevance
“…An increased level of arginine has been reported in rice leaves after drought stress [73]. Also, Aninbon et al(2017) reported high arginine content in peanuts after drought stress [74]. Conversely, in our results, arginine content significantly decreased drought leaves compared to the control.…”
Section: Organic Acids Metabolic Changes To Drought Stresscontrasting
confidence: 45%
“…An increased level of arginine has been reported in rice leaves after drought stress [73]. Also, Aninbon et al(2017) reported high arginine content in peanuts after drought stress [74]. Conversely, in our results, arginine content significantly decreased drought leaves compared to the control.…”
Section: Organic Acids Metabolic Changes To Drought Stresscontrasting
confidence: 45%
“…In particular, a spring wheat cultivar (Bahar cv) display increased levels of proline, arginine and lysine in drought stress [36]. In addition, a peanut study found that drought increased the amount of arginine in all genotypes [37]. In a study of Triticeae species to compare metabolite profiles of drought stress, alanine was found to increase exposure to drought stress [38].…”
Section: Discussionmentioning
confidence: 99%
“…An increased level of arginine has been reported in rice leaves after drought stress [ 68 ]. Also, [ 69 ] reported high arginine content in peanuts after drought stress. Conversely, in our results, arginine content significantly decreased in drought leaves compared to the control.…”
Section: Discussionmentioning
confidence: 99%